Designing Tebing Tinggi City Hotel with Regionalism Architecture Approach - Harisdani, Devin Defriza; Santoso, Nailah (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Tebing Tinggi City has a strategic position outlined in the RPJMD 2011-2016, with a cross-Sumatra road network connecting Medan, Parapat, and Medan-Rantau Prapat and Medan-Siantar railroad networks. Kuala Namu Airport, Tebing Tinggi-Kuala Namu toll access, Kuala Tanjung International Port, and Sei Mangke industrial area encourage development. The RPJP vision of Tebing Tinggi City as a